Psychopharmacology for Nonpsychiatrists A Primer - Greenfield, Daniel P.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
This unique, easy-to-read title offers a concise, practical guide to psychopharmacology and psychopharmacotherapy. Designed for a wide range of practitioners and trainees in general and mental healthcare, this invaluable primer provides foundational information for those who wish to cultivate a deeper understanding of the often-mysterious psychopharmacology medication family. Unlike other books on this topic, the primer positions psychopharmacology within the larger context of psychiatric and psychological treatment and also discusses the variety of therapeutic and somatic techniques available to providers and their patients. Further, since many patients with psychiatric conditions unfortunately find themselves interacting with the justice system, the author offers useful considerations related to the intersection of mental health and the law. The primer consists of 13 chapters and is organized in four parts: Part 1 covers essentials of pharmacology and psychopharmacology, outlining the basic principles of pharmacology, psychopharmacology, and psychopharmacotherapy. Part 2 addresses therapies that may involve psychopharmacology/ psychopharmacotherapy, providing a succinct overview of selected and representative types of psychotherapy and counseling in contemporary psychiatry and psychology. Part 3 discusses forensic and legal applications of psychopharmacology/ psychopharmacotherapy, drawing on the author$1 (Bs long experience in various aspects of forensic psychiatry. Part 4 consists of one final chapter, titled (3z(BSynthesis and Conclusions.(3y (BThis chapter pulls together the most salient points of the book to assist the reader in the practical psychopharmacotherapeutic treatment of patients/clients. A timely and invaluable contribution to the literature, Psychopharmacology for Non-Psychiatrists: A Primer will be of great benefit as a user-friendly resource for professionals or as an exam-preparation book for medical students and trainees in a wide range of mental health fields. Specifically, the primer will be of great interest to primary care physicians, nurse practitioners, physician assistants, counselors, therapists, non-psychiatric physicians and dentists whose practices involve psychopharmacotherapy, naturopaths, homeopaths, physical therapists, occupational therapists, and speech/language therapists. Legal professionals and others who are not themselves healthcare professionals, but who interact with healthcare professionals, also will find the primer a handy resource.s
Introduction: Epidemiologic Triangle Model, Diagnosis, Psychiatric Diagnosis, and Other Necessary Preliminaries -- Basic Principles of Pharmacology, Psychopharmacology, and Psychopharmacotherapy -- The Four (3z(BMajor Anti-s(3y (B-- The Sixteen (3z(BMinor Anti-s(3y (B-- Illicit Substances and Drugs -- Botanicals, Herbals, Nutraceuticals and (Dietary) Supplements -- A Selective Overview of Therapies In Psychiatry and Psychology -- Psychotherapies and Counseling -- Somatic Therapies (Somatotherapies) -- Overview -- Selection and Use of Experts: Five Questions -- Evaluating vs. Treating Doctor/Therapist: A Word To The Wise -- Synthesis and Conclusions.s
Keywords: Psychiatry; Psychiatry; Psychopharmacology